Iscensättning av läkekonster i folkhemmet: Läkare och kvacksalvare i svenska folklustspel decennierna kring 1900-talets mitt - Eklöf, Motzi (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2007)
The image of the doctor established by cultural and medical history is that of a great authority who was held in high esteem during a large part of the 20th century but whose halo became somewhat tarnished during the final 25 years. The question is whether this image is generally valid. In whose eyes was the doctor a great authority and in what respect? With the aim of studying the image of the doctor and his supposed antithesis — the quack — from a folk perspective, Swedish burlesque comedy published from 1930 through the 1950s has been studied here. In this genre originating from the folk humor of the Middle Ages, in the spirit of Rabelais, and scoffed at by the upper classes of society, the quack has a more prominent role than the doctor, and he uses the same agents, although they are simpler and more twisted. A medical moral that can be extracted from the theatre productions is that the doctor is hardly credited with better curative powers than the quack. On the other hand, the new generation’s doctor represented a promise for the future regarding higher ethical standards and thereby better medicine right from the start. That relatively little importance was attributed to practical healing arts and treatment capabilities in the creation of the medical profession’s ethos certainly contributed to the fact that people also turned to other types of practitioners.